Influence of Environmental Temperature on Thyroid Hormone Production in Sheep - Syafwan, Syafwan (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
The effect of high (28oC) and low (14oC) temperature on thyroid hormone production were studied in five male sheep since the activity of thyroid releasing hormone (TRH) cell in the hypothalamus that influence the thyroid stimulating hormone (TSH) production and release can be affected through the temperature regulatory center. The aim of this study were to measure the iodine (the core of thyroid  hormone)  needed  in  the  different  temperatures,  T4 (thyroxine) production, T4 and T3 (triiodotironine) concentration. Two experiments were performed  in  both  condition  to  investigate  the  thyroidal 125 I  uptake  and  to measure  T4 production.  The  sheep  were  shorn  at  the  beginning  of  each adaptation period (22o C). The first  treatment was  high  temperature and  the second treatment was low temperature. The experiments were done at least five weeks of each temperature. The mean of rectal temperatures during the warm period were significantly higher than that in the cold period. The feed intake during the warm period tend to decrease significantly, but there was no increase during the cold period. The absolute iodine uptake (AIU) over 24 hours was markedly increased during the second period (7.94±1.37 -g/24 hr) compare to the first period (1.65±0.13 -g/24 hr). It means that cold exposure has a potential to stimulate the thyroid gland in order to uptake more iodide. The mean of T4 concentration  was 51.6±2.1 ng/ml during the warm and 61.2±5.5 ng/ml four weeks after shift to the cold period and did not differ, but four weeks later the concentration  was  significantly  increased  (77.4±1.47)(33%).  The  same  pattern occurred to the T3 concentration that the four weeks after shifting the level of T3 was not significantly increased from value of 0.39 ng/ml to value of 0.51 ng/ml, eight weeks after shifting the T3 value (0.65 ng/ml) was significantly rose. This